2023
DOI: 10.1186/s13578-023-01054-y
|View full text |Cite
|
Sign up to set email alerts
|

SETD8, a frequently mutated gene in cervical cancer, enhances cisplatin sensitivity by impairing DNA repair

Abstract: Background Cisplatin is commonly used to treat cervical cancer while drug resistance limits its effectiveness. There is an urgent need to identify strategies that increase cisplatin sensitivity and improve the outcomes of chemotherapy. Results We performed whole exome sequencing (WES) of 156 cervical cancer tissues to assess genomic features related to platinum-based chemoresistance. By using WES, we identified a frequently mutated locus SETD8 (7%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…However, the role and the regulatory mechanism of SETD8 in ES remain unknown. In the current investigation, we observed that the expression of SETD8 was elevated in ES, corroborating prior findings that SETD8 is overexpressed across a spectrum of malignancies, including neuroblastoma [ 13 ], pancreatic carcinoma [ 12 ], cervical cancer [ 24 ], multiple myeloma [ 25 ], and colorectal cancer [ 14 ]. Additionally, our findings indicate a strong correlation between elevated SETD8 expression and reduced OS and EFS in patients with ES, underscoring the clinical relevance of SETD8 in this context.…”
Section: Discussionsupporting
confidence: 90%
“…However, the role and the regulatory mechanism of SETD8 in ES remain unknown. In the current investigation, we observed that the expression of SETD8 was elevated in ES, corroborating prior findings that SETD8 is overexpressed across a spectrum of malignancies, including neuroblastoma [ 13 ], pancreatic carcinoma [ 12 ], cervical cancer [ 24 ], multiple myeloma [ 25 ], and colorectal cancer [ 14 ]. Additionally, our findings indicate a strong correlation between elevated SETD8 expression and reduced OS and EFS in patients with ES, underscoring the clinical relevance of SETD8 in this context.…”
Section: Discussionsupporting
confidence: 90%
“…The roles of SETD8 and SYMD2 in chemoresistance have been reported by various groups. For example, melphalan resistance in multiple myeloma, cisplatin resistance in cervical cancer, and docetaxel resistance in hepatocellular carcinoma were all associated with SETD8 [ 44 46 ]. Similarly, SYMD2 enhanced oxaliplatin resistance in SW620 CRC cells by inducing the expression of drug efflux transporters [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Primary or acquired resistance to chemotherapy is a major barrier to breast cancer treatment. The main reasons for chemotherapy failure include (a) inadequate pharmacokinetic properties of the drug [29]; (b) tumor cell-intrinsic factors, such as the expression of drug e ux pumps, altered cellular homeostasis, and glucose metabolism; and (c) the tumor microenvironment, characterized by hypoxia and acidosis [30]. The mechanism of docetaxel resistance in breast cancer is multifaceted.…”
Section: Discussionmentioning
confidence: 99%